“A study of Occupational stress among teachers teaching in secondary schools” (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2026)
Teacher is an important part of the school. He builds healthy minds of students with his knowledge and skills. Nowadays teaching is considered a stressful profession. According to the National Institute for Occupational Safety and Health (NIOSHA 1998), occupational stress is a harmful physical and emotional reaction. It occurs when the requirements of the job do not match the worker's ability, resources or needs. Occupational stress also has a bad effect on health. The British Mental Health Charity (MIND) states that “if you frequently experience feelings of stress, you may be at risk of developing a mental health problem such as depression or anxiety, and stress can also worsen existing problems.” In today's times, teachers' work has increased in emotional, physical, administrative and management duties, as well as parental demands and wants, uncomfortable working conditions, co-curricular activities, meetings, extra classes to attend and unnecessary paperwork. In this study, the professional stress of teachers teaching in secondary schools has been studied. In this study, 100 teachers from secondary schools of Patna district have been selected by purposive method. Self-made and validated questionnaire has been used for data collection. Mean, standard deviation and t-test have been used for data analysis. After analysing the results, it is found that there is a significant difference in the professional stress of teachers teaching in secondary schools on the basis of type of school (government and private). Hence, there is a difference in professional stress of both the groups and on the basis of gender (male and female), there is also a significant difference in the professional stress of teachers teaching in secondary schools i.e., a difference was found in the professional stress of both the groups